Childhood cancer in developing society: A roadmap of health care - Ramesh, P M; Marwaha, R K; Anish, T S (Indian Journal of Medical and Paediatric Oncology, 2011)
Background: We assessed referral patterns of children with hematological malignancies (HM) in North India. Materials and Methods: The parents/guardians were interviewed at presentation, in the period between October 2001 and November 2002. Patient delay (symptom-contact), health system delay (contact-diagnosis), total delay (symptom-diagnosis), and number of contacts were compared between high- and standard-risk disease group. Results: Of the 79 children (55 boys; 69.6%) with HM, 47 (59.5%) had Acute Lymphoblastic Leukemia (ALL). Forty-four children had high-risk disease. The patient, system and total delay were a median of 2 days (with Interquartile range IQR of 1−6), 37 days (IQR 13−55), and 38 days (IQR 15−60) respectively. Majority of patients (64/79; 81%) went to private sector (non governmental health care providers) for health care. Number of contacts, which was the most significant, correlate with system delay. Conclusions: Sensitizing the private sector practitioners about cancer in symptomatic children (pallor, bleeding, fever) may be effective.
Keywords: Childhood cancer; epidemiology; patient delay; referral delay